Law, bioethics and society: Jewish and Islamic approaches to fertility treatments and human germline genome editing - Goodwin, Vanessa (The University of Edinburgh, 2023)
In 2018, the Chinese biophysicist He Jiankui announced the birth of the first genetically modified babies; this broke an international moratorium. When the Russian biologist Denis Rebriko reported similar intentions, ethicists and legislators began working with an increased sense of urgency towards a global framework to define the limits of Human Germline Genome Editing (HGGE). This is because HGGE poses concerns for the safety of future generations, and reproductive tourism has the potential to undermine the legislation of any one country. Whilst secular international bioethics councils aim to find global consensus on this matter, religious jurists and bioethicists, though influential in their own communities, are not necessarily part of the same international debate. The thesis proposes that the influence of religious law is considerable on societies, legislation and on fertility practices, especially in Israel and the Muslim Middle East, so the inclusion of religious legal viewpoints is an important aspect of any global consensus on bioethical issues. In Judaism and Islam the field of bioethics is a subcategory of contemporary religious law. As the legal narratives of Jewish law (Halakha) and Islamic law (Shari’a) are complex, the legal reasoning and influence of religious jurists has to be understood within their religious paradigm if they are to be successful integrated in the international debate. The thesis investigates the process by which contemporary Orthodox Jewish and Muslim jurists engage with the bioethical questions of reproductive medicine in general in order to understand their specific response to the potential permissibility of HGGE. It enquires how the religious legal systems have already adapted to reproductive technologies and how the legislation of fertility treatments in Israel and the Muslim Middle East incorporates the values and legal guidelines of Halakha (Jewish law) and Shari’a (Muslim law). The thesis is divided into three parts. Parts I and II introduce the mechanisms by which Halakha and Shari’a respectively engage with new legal cases as a result of medical and scientific advancements and then explore the sociological context of applied Jewish and Muslim bioethics in the Middle East. Part III charts the development of the key legal debates concerning fertility treatments from the late twentieth century onwards in Orthodox Judaism and in Islam. It focuses on three reproductive technologies: 1.) Artificial Insemination with Donor sperm (AID) 2.) In Vitro Fertilisation (IVF) and 3.) Pre-Implantation Genetic Diagnosis (PGD). It finds that the legal opinions of prominent jurists in the late 20th century set precedents for all subsequent debates in both religious legal traditions including the current debate about the permissibility of HGGE. This evolving engagement of scientists and religious jurists demonstrates how Halakha and Shari’a both have normative legal principles that are rooted in the Torah, the Qur’an and in the wider scriptural tradition in both faiths. Legitimate conception and lineage retain their central importance in all debates about fertility treatments. However, the legal traditions have adapted significantly in the face of emerging reproductive medicine and the wider societal and ethical implications for the rights of the parent and the child. Finally, this research studies the rapid acceptance of genetic screening programs in Israel and the Middle East and highlights the different approaches to the genetic improvement of societies. It finds a religious narrative which endorses the deselection of pre-embryos as an ethical alternative to abortion and explores how this may impact future debates about the permissibility of HGGE. Given this context it becomes apparent how Jewish and Muslim jurists debate the fundamental questions about the creation of human life and why their divergent legal judgements, which are generated for the moral good of their respective societies, matter in the global debate.
Keywords: comparative religious bioethics; reproductive medicine; medical ethics; Jewish bioethics; Islamic bioethics